Philippines : Background Papers. (IMF Staff Country Reports; Country Report ;, 1995)
This Background Paper analyzes the Philippines's experience with capital inflows. It compares the episode of 1993-95 with the pre-debt crisis period, and makes the case that the recent inflows are in important respects more benevolent than in the past. The paper concludes that inflows are consistent with a balanced and sustainable revival in the Philippines economy, and indeed are most likely contributing to recovery. This paper also examines financial reintermediation and new challenges to monetary policy. Requirements and plans for the fiscal reform in the medium term are also described.